Application of NDT thermographic imaging of aerospace structures - Deane, Shakeb; Avdelidis, Nicolas P.; Ibarra-Castanedo, Clemente; Zhang, Hai; Yazdani Nezhad, Hamed; Williamson, Alex A.; Mackley, Tim; Davis, Maxwell J.; Maldague, Xavier P.; Tsourdos, Antonios (Elsevier, 2019)
This work aims to address the effectiveness and challenges of Non-Destructive Testing (NDT) inspection and improve the detection of defects without causing damage to the material or operator. It focuses on two types of NDT methods; pulsed thermography and vibrothermography. The paper also explores the possibility of performing automated aerial inspection using an unmanned aerial vehicle (UAV) provided with a thermographic imaging system. The concept of active thermography is discussed for inspecting aircraft CFRP panels along with the proposal for performing aerial inspection using the UAV for real time inspection. Static NDT results and the further UAV research indicate that the UAV inspection approach could significantly reduce the inspection time, cost, and workload, whilst potentially increasing the probability of detection.
Keywords: active infrared thermography; pulsed thermography; vibrothermography; UAV; Composite; kissing bond